IL6 and BCL3 Expression Are Potential Biomarkers in Esophageal Squamous Cell Carcinoma - Soares-Lima, Sheila Coelho; Gonzaga, Isabela Martins; Camuzi, Diego; Nicolau-Neto, Pedro; Vieira da Silva, Raissa; Guaraldi, Simone; Ferreira, Maria Aparecida; Hernandez-Vargas, Hector; Herceg, Zdenko; Ribeiro Pinto, Luis Felipe (Frontiers in Oncology, 2021)
Esophageal squamous cell carcinoma (ESCC) ranks among the most lethal tumors worldwide, as a consequence of late detection and poor treatment response, evidencing the need for diagnosis anticipation and new therapeutic targets. First, we investigated the IL6 gene and protein expression in the esophagus of individuals without esophageal disorders (healthy), ESCC, and non-tumoral surrounding tissue (NTST). Our results showed that IL6 mRNA and protein expression is overexpressed in tumor cells relative to NTST. In the TCGA dataset, we identified a set of genes whose expression was correlated with IL6 mRNA levels, including the antiapoptotic gene BCL3. By using an immortalized esophageal cell line, we confirmed that IL6 was capable of inducing BCL3 expression in esophageal cells. BCL3 mRNA and protein are overexpressed in ESCC and NTST compared to healthy esophagus, and BCL3 mRNA could distinguish the morphologically normal samples (healthy and NTST) with 100% sensitivity and 95.12% specificity. The spatial intratumoral heterogeneity of both IL6 and BCL3 expression was evaluated, corroborating IL6 upregulation throughout the tumor, while tumor and NTST showed a consistent increase of BCL3 expression relative to the healthy esophagus. Our study shows that IL6 overexpression seems to be a key event in ESCC carcinogenesis, contributing to ESCC through a homogeneous antiapoptotic signalling via BCL3 overexpression, thus suggesting anti-IL6 therapies to be further considered for ESCC treatment. Finally, our data support the use of BCL3 mRNA expression as a potential biomarker for ESCC detection.